The adventure gap : changing the face of the outdoors - Mills, James Edward, 1966- (Mountaineers Books, 2024)
"Outdoor journalist James Edward Mills's book, The Adventure Gap, is a groundbreaking volume that is equal parts adventure story, history, and inspiration as it chronicles the first American all-Black summit attempt on Denali in 2013. Mills uses this momentous expedition as a jumping-off point to explore diversity in the outdoors, from Mathew Henson who stood at the North Pole in 1909 to contemporary adventurers such as polar explorer Barbara Hillary and rock climber Kai Lightner. This 10th Anniversary Edition once again shares the compelling events that unfolded during Expedition Denali's summit bid. But it also provides fresh context: A new, thought-provoking afterword by Mills examines what has evolved in and around the outdoor community since that effort. He highlights progress and inspiring stories, such as Full Circle Everest, an expedition lead by Phillip Henderson that put an all-Black team on top of the world's highest peak. And he points to places where we can and should all strive for higher achievement"--